Presenting a Model for Developing Organizational Citizenship Behavior in Iraqi Secondary School Teachers - Maha Mohammed Abbas AL-KHATEEB; Kobra Emami Rizi; MUNA MOHAMMED ABBAS AL-KHATEEB; Narges Saeidian Khorasgani (مدیریت و چشم انداز آموزش)
Abstract The aim of this study is to present a model for developing organizational citizenship behavior in Iraqi secondary school teachers. The research method is applicable in accordance with its purpose, and its method is qualitative and data-based. The statistical population consists of 15 secondary school teachers and experts related to the subject, selected through theoretical sampling, and the selection of samples continued until theoretical saturation. The data collection tool is a semi-structured interview. For data analysis, the data-based method and Atlas ti8 software were used, and open, axial, and selective coding stages were used to identify and classify the main and sub-categories. The findings showed that teachers' organizational citizenship behavior includes key dimensions such as organizational cooperation, professional development, respect and values, commitment and responsibility, educational innovation, honesty and feedback, well-being and mental health, encouragement of academic growth, and discipline and adherence to principles. These dimensions are presented as a comprehensive model and are proposed as a framework for strengthening these behaviors. The present study shows that strengthening organizational citizenship behavior in teachers not only leads to improving the educational environment and increasing the motivation of teachers and students, but also has a positive impact on the overall performance of the educational system. Introduction Today, the completely changing conditions prevailing in organizations have increased competition in them, which makes the need for their effectiveness in such conditions more evident than ever before. This refers to the generation that is referred to as organizational soldiers, and these employees are undoubtedly the distinguishing feature of effective organizations from ineffective ones; that is, employees who tend to go beyond the formal requirements of their jobs, which is called organizational citizenship behavior, and has received increased attention from managers and organizational officials in recent years (Rezazadeh, 2019). Organizational citizenship behavior is one of the new concepts of organizational behavior management that emphasizes the extra-role behaviors of employees and managers and plays a fundamental and decisive role in the organizational process and transforming the traditional and static environment into a dynamic and efficient environment. Therefore, if successful and unsuccessful organizations take steps to create organizational citizenship behavior, their organizational efficiency and productivity will increase, and this will improve their performance compared to competing organizations (Zareatn Dolatabadi et al, 2022). Since organizational citizenship behaviors directly affect the quality of education and student learning outcomes, examining these behaviors and identifying the factors affecting them can help improve educational systems. As a result, more research in this field can lead to constructive changes in educational environments and lead to an overall improvement in the state of education worldwide. Therefore, the researcher seeks to answer the question: what is the model for developing organizational citizenship behavior in Iraqi secondary school teachers? Theoretical Framework Organizational Citizenship Behavior Organizational citizenship behavior refers to a set of voluntary and discretionary behaviors that are not part of an individual's formal duties but are performed by the individual and improve organizational tasks and roles and the growth and development of organizational performance (Alwi et al, 2021). Choong & Peng Ng (2024) examined the shaping of teachers' organizational citizenship behavior through self-efficacy and trust in colleagues: the moderating role of collective efficacy. The results indicate that trust in colleagues has a positive relationship with organizational citizenship behavior and teacher self-efficacy. In addition, teacher self-efficacy and organizational citizenship behavior are also positively related. Furthermore, the relationship between trust in colleagues and organizational citizenship behavior is partially mediated by teacher self-efficacy. In addition, collective efficacy significantly moderates the path between teacher self-efficacy and organizational citizenship behavior, but not between trust in colleagues and organizational citizenship behavior. Mousavifard (2024) investigated the effect of intellectual capital and strategic leadership on organizational citizenship behavior with the moderating role of professional ethics of employees in the General Directorate of Education of Kermanshah Province. The findings showed that intellectual capital has a significant and positive effect on organizational citizenship behavior by 66 percent. Strategic leadership predicted changes in organizational citizenship behavior by 46 percent; also, the moderating role of professional ethics of employees between intellectual capital and strategic leadership with organizational citizenship behavior was confirmed, with the moderating rate of this variable being 5 percent and 3.2 percent, respectively. The results showed that intellectual capital has a greater effect on organizational citizenship behavior than strategic leadership. Therefore, it is necessary to pay more attention to intellectual capital in order to improve organizational citizenship behavior in the organization. Research Methodology The research method is applicable due to its purpose, and its method is qualitative and data-based. The statistical population consists of 15 secondary school teachers and related experts selected through theoretical sampling that continued until theoretical saturation was obtained. The data collection tool is a semi-structured interview. Research findings For data analysis, the data-based method and Atlas ti8 software were used, and open, axial, and selective coding stages were used to identify and classify main and sub-categories. The findings showed that teachers' organizational citizenship behavior includes key dimensions such as organizational collaboration, professional development, respect and values, commitment and accountability, educational innovation, honesty and feedback, well-being and mental health, encouragement of academic growth, and discipline and adherence to principles. These dimensions are presented as a comprehensive model and are proposed as a framework for strengthening these behaviors. The present study shows that strengthening organizational citizenship behavior in teachers not only leads to improving the educational environment and increasing the motivation of teachers and students, but also has a positive impact on the overall performance of the education system. Conclusion The present study was conducted with the aim of presenting a model for developing organizational citizenship behavior in Iraqi secondary school teachers. The results of this study are consistent with the results of Choong & Peng Ng (2024), Mousavifard (2024), Behkesh & Behkesh (2024), Ghanbari et al, (2023), Nguyen Iran (2023), Ghanbari & Ahmadi (2022), Zarean Dolatabadi et al, (2021), and Hadipur (2019). Behkesh & Behkesh (2024) showed that organizational citizenship behavior is a constructs that has been of interest for a long time and the subject of much research. Given the specific conditions of the primary school, teachers of primary school have the most important responsibility. Teachers of this level have special duties to increase productivity and, as a result, the success of students in school. We have explained the importance of organizational citizenship behaviors, the characteristics of organizational citizenship behaviors, and its dimensions. An effective teacher is a teacher who can play a positive role in the intellectual and moral development of students. In order to make progress in education and training, primary school teachers must have high organizational citizenship behaviors. According to the results of the research, the following suggestions were made: One of the most important suggestions is that schools and educational centers should focus on strengthening cooperation and positive interaction between teachers and other members of the teaching staff. For this purpose, holding team-building workshops and training programs to improve communication skills and promote a spirit of cooperation can play a significant role in strengthening organizational citizenship behavior. Also, supporting teachers by providing continuous learning and professional development opportunities such as training courses, conferences, and study groups can help improve teaching performance and interpersonal communication in schools.